Phenology of Anemonia viridis and Exaiptasia diaphana (Cnidaria: Anthozoa) from marine temperate ecosystems - Di CAMILLO, GIOIA CRISTINA; AROSSA, SILVIA; PICA, DANIELA; AZZURRA, BASTARI; TORSANI, FABRIZIO; CERRANO, CARLO (Mediterranean Marine Science, 2021)
Population dynamics in lower metazoans are strongly regulated by environmental factors. The current climate crisis could affect regularity of life strategies; therefore, studying life cycles and reproductive patterns of benthic species may provide key information on effects of environmental changes in temperate seas. The North Adriatic Sea is a peculiar basin due to high food availability and high fluctuations of physical parameters. Here, cnidarians are one of the most abundant taxa, and sea anemones are the largest representatives. Aim of this study is to assess the life history and the reproductive biology of two potential species models: the sea anemones: Anemonia viridis and Exaiptasia diaphana. The present research is the first quantitative study on the variations in abundance and reproductive biology of the two species. We reported new insights about abundance fluctuations throughout the year and about the gametogenesis of the two sea anemones. In particular, data on spermatogenesis of A. viridis from the Mediterranean Sea were supplied for the first time.